CULTURAL ISSUES IN PERSONEL SELECTION - Bagus Riyono (Faculty of Psychology Universitas Gadjah Mada, 1998)
Personnel selection is an important part of organization system and processes. It is the primary element of organizational processes. If an organization fail in this first step, the subsequent processes will not be effective.